Posttreatment of olive mill wastewater by immobilized TiO2 photocatalysis - Costa, J. C. (2013)
A photocatalytic reactor with UV/TiO2 was used for the post-treatment of olive mill wastewater after anaerobic digestion. A factorial experimental design was adopted to determine the statistical significance of each parameter tested, namely initial COD, pH, treatment time and recirculation flow, and possible interactions, in three response variables: phenols, colour, and COD removals. Removal efficiencies of 90.8 ± 2.7 %, 79.3 ± 1.9 %, and 50.3 ± 6.3 % were obtained for total phenols (TPh), colour, and COD, respectively. TPh and colour were almost completely removed after 24 h of treatment, while the COD removal was partial. Because increasing the treatment time is economically unfeasible a recirculation to the anaerobic reactor should be considered. Regarding the most significant variables, the TPh removal efficiency is dependent of the initial COD concentration; the colour removal efficiency decreased with increasing COD concentration and pH; and, the COD removal efficiency is directly linked with the treatment time. The interaction between the initial COD and treatment time affect negatively the response variables tested because of the inactivation of some active sites of the TiO2 paper.